Review of Patch Antennas used in Drone Applications - M. M. Hasan Mahfuz; Chan-Wang Park (IEEE Access, 2023)
Drones are a form of remote-controlled aircraft that can take to the air without the need for a human pilot. An increasing number of people are looking into using drones for a variety of tasks, including but not limited to operations in hazardous areas, environmental monitoring and sensing, aerial spreading of fertilizer and agricultural chemicals, disaster management and transporting goods from one location to another. Drones are receiving a lot of attention for these and other uses. A drone’s position and navigation can only be controlled by the remote pilot via radio frequency (RF) transmission between the drone and the remote pilot. In order to facilitate two-way communications between the drone and its operator, it is necessary to keep a tight eye on the telemetry data and supplementary sensor data being sent and received by the drone in real time. Unmanned flying would not be conceivable without a flexible and dependable communication system. Due to the necessity of complete spatial coverage for drone communication, the antenna radiating in an isotropic pattern presents itself as a promising option for unmanned flying. Therefore, microstrip patch antenna is an excellent choice for drone applications.